Intradialytic Hypertension in End Stage Renal Disease patient : Prevalence and clinical characteristic - Margaret Merlyn; Akhil Deepak Vatvani (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Introduction : Intradialytic hypertension (IDH) is common and it increases the incidence of cardiovascular morbidity and mortality, however this is often ignored. The aim of this study is to identify the prevalence of IDH and compare the clinical characteristics of patients with and without IDH.Methods : A cross sectional study was carried out in 3 hemodialysis clinics in Jakarta, Indonesia. We compared several clinical characteristics inpatients with IDH and control group without IDH. Nutritional status was also assessed using Subjective Global Assessment (SGA). IDH was defined as >10 mmHg increase in systolic blood pressure (BP) in at least four of six prior consecutive hemodialysis sessions. Student’s T-test or Mann-Whitney test was used to compare the quantitative variables. Chi-Square or Fischer exact test was used to compare categorical variables.Results : A total of 114 patients was included in this study. There were 86 (62.3%) male patients. IDH was present in 47 (34.1%) patients. The mean age in IDH and control group were 53.4 (±13.2) and 52.8 (±12.4) years respectively (p: 0.800). The mean BMI of IDH and control group were 21.8 (±3.7) and 24.0 (±4.4) kg/m2 respectively (p: 0.031). The mean MAP during dialysis of IDH and control group were 108 (±13.1) and 98.6 (±23.2)mmHg respectively (p: 0.011). The median creatinine levels of IDH and control group were 8.1 (3.02-22.20)mg/dl and 10.8 (2.89-22.0)mg/dl respectively (p: 0.008). Interestingly, moderate to severe malnutrition status had significant association with IDH (OR: 2.31, p: 0.031). Patients who undergo dialysis thrice a week was associated with IDH rather than patients who undergo dialysis twice a week (OR: 2.27, p: 0.035).Conclusion : The prevalence of IDH is higher than previously reported in other countries. The clinical characteristic of patients with IDH is lower BMI, higher MAP and lower creatinine levels than in patient without IDH. Moderate to severe malnutrition and frequency of dialysis per week had significant association with IDH.